Kepemimpinan yang Melayani di Sekolah Kristen dalam Pengelolaan Organisasi, Pengelolaan Stres, dan Integritas [Servant Leadership in Christian Schools Through the Organization Management, Stress Management, and Integrity] - Kurnia, Rieswan Pangawira (Universitas Pelita Harapan, 2020)
Leadership is needed in everyone’s organization and one effective type of leadership is servant leadership. In Christian schools, leaders can apply servant leadership which can be a good example and a blessing to the people around them. Leaders’ understanding and implementation of servant leadership were examined in Christian schools, while leaders’ characteristics in managing the organization, in managing stress, and integrity were examined in carrying out their leadership function in schools. A descriptive qualitative research method through semi-structured interviews with school leaders was used. Coding and data triangulation techniques through interview with leaders, interviews with teachers, and questionnaires. This study was conducted on six leaders in four Christian schools in Jakarta and surrounding areas. It was found that leaders understand servant leadership by centering on the Lord Jesus and implement servant leadership by sharing their power, prioritizing others’ development, and loving one another. Organizational management requires the same vision and mission, good relations, the ability to manage, and the coaching of teachers. Stress management requires consistent faith discipline and closeness with God, keeping life balanced and encouraging one another. Leaders’ integrity should be upheld by setting an example of honesty, humility, sacrifice, and a close relationship with God.